Faktor Risiko Yang Berhubungan Dengan Kejadian ISPA Pada Balita di Kelurahan Cijoho Wilayah Kerja Puskesmas Kuningan Tahun 2017 - Nengsih, Neneng Aria; Saprudin, Nanang; Arief, Lisa Novita (Jurnal Ilmu Kesehatan Bhakti Husada: Health Sciences Journal, 2017)
ISPA is kind of disease it might infected. ISPA also kind of disease are still exsist and its become a big issue of global in all countries. The case of ISPA to an infants in Kuningan now isreach of 69,17% in area of work central population (PUSKESMAS) in the village of Cijoho Kuningan its become number 1 intotal of infants and tis is most highhest ranking of diseas in years 2015-2016 withISPA. The reason in this case is explain to analysis the factor of risk which combinate its happening ti ISPA for infants in the village of Cijoho working area Puskesmas Kuningan 2017. Type of reserch is quantitative analytic survey with design cross-sectional. The sample 250 infants with sampling techniques Proportionate Stratified Random Sampling. Research instrument used is the weight scale,measuring height, questionnaries and obsevation sheets that have tesed the validity. Data analysis using standard chii-square with significant (0,05). Factor whice combine with ISPA its happening to infants within research when in the family is smoking with p-value = 0,011 given breast feeding exclusiv of p-value = 0,017, in status of protein, the result of imunisation, the knowledge of being mother is not combine with the meaning of ISPA to the infants in the village of Cijoho working are Puskesmas Kuningan 2017. Informing the message to all mother who have an infants to more cares and given breast feeding exclusiv within 0-6 months and contynuesly until 2,5 years old of your infants, so your baby is not easy to have a virus or bacterial in any mamber in your family is smoking inside of the house, so please to stop it to avoid negativ health to your infants.